(untitled) (Research, Society and Development, 2024)
The success of tooth movement in treating traumatized teeth depends on the severity of the initial injury. The objective of this study was to evaluate the histological structure of periodontal tissues and root resorption during orthodontic movement of traumatized teeth. A total of 24 female Wistar rats were used and divided into four experimental groups: Group 1, 6 rats that were not subjected to any experimental procedure (control); Group 2, 6 rats that were subjected to induced tooth movement (ITM); Group 3, 6 rats that underwent dentoalveolar trauma (DT); and Group 4, 6 rats that were subjected to DT+ITM. At the end of the experimental period, the animals were euthanized, and the maxilla were removed and processed for histology. Has been observed that the animals in the DT+ITM group had a significantly higher tooth movement rate than the animals in the ITM group. The animals of CTL group had normal findings, while alterations were found in the remaining animals. In ITM group, disorganization of the periodontal ligament (PL) and vascular changes, in addition to moderate root resorption, were observed. The DT group also demonstrated these changes, in addition to presenting with giant cells in the furcation region. In DT+ITM group, in addition to the findings seen in the other experimental groups, also presented with PL disorganization, moderate vascular changes, more intense root resorption and hyaline areas. We conclude that of induced tooth movement associated with the extrusive subluxation trauma causes increases the rate of tooth movement and root resorption.